Load and recovery monitoring in top-level youth soccer players: exploring the associations of a web application-based score with recognized load measures - Anderegg, J.; Brefin, S.; Nigg, C.; Koschnick, D.; Paul, C.; Ketelhut, S. (European Journal of Sport Science, 2025)
This study investigates the relationship between a web application-based load and recovery score (LRS) and established load parameters. Seventy-eight elite youth soccer players were recruited from a single top-tier Swiss club. All participants were healthy and injury-free at baseline and actively competing at the highest national youth level, participating in five training sessions per week. Players with recent injuries or chronic health conditions were excluded. Seventy-one players (32.4% female) with an average age of 18 years (SD = 1.2) met the inclusion criteria and were monitored throughout = 35 days, applying a repeated-measure design. Daily assessments of the self-reported LRS, along with measurements of player and trainer session ratings of perceived exertion, total distance covered, and total distance > 20 km/h, were collected. Linear mixed-effects models were used to analyze the influence of load parameters on the following day's LRS. All training and match load parameters demonstrated significant negative correlations with the subsequent day's LRS. Player and trainer session ratings of perceived exertion had similar fixed effects (-0.013, 95% CI [-0.017, -0.010] vs. -0.008, 95% CI [-0.011, -0.006]), whereas total distance covered exhibited stronger associations (-0.668, 95% CI [-0.979, -0.355]) than total distance > 20 km/h (-0.009, 95% CI [-0.012, -0.006]). The impact of the different load parameters varied across groups and individuals. The LRS provides an easy-to-use digital tool that summarizes multiple training and recovery factors into one score, helping coaches and staff monitor player readiness in daily field settings. By offering accessible daily feedback, the LRS may help tailor training loads, manage recovery, and reduce the risk of overtraining and injuries.